Adaptive Market Efficiency: Evidence from the South African Stock Market - Masangu, Ishmael Fanelo (University of the Witwatersrand, Johannesburg, 2024)
This study examines the adaptive market hypothesis in the Johannesburg Stock Exchange market by test- ing for stock return predictability using daily data from January 1996 to December 2023 across six differ- ent indices. The study applies three linear and three nonlinear tests to check if the Johannesburg Stock Exchange market is efficient, moving towards efficiency, switching to efficiency/inefficiency, adaptive and inefficient. The overall findings of this study provides compelling evidence that stock returns within the Johannesburg Stock Exchange market across the six indices are inefficient, as indicated by significant evidence of inefficiency, non-randomness, the presence of serial correlation and nonlinear effects in the six tests performed. These results challenge the notion of the weak-form of market efficiency and suggest that past prices of stock returns are related to future prices, indicating the presence of predictability and exploitable opportunities within the JSE market.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Market efficiency; adaptive market hypothesis; efficient market hypothesis; random walk; weak-form of efficiency; efficiency; JSE; SDG-8: Decent work and economic growth